Sweet Dew Since 1980 : Special Project for the 20th Anniversary of the Gwangju Biennale - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2014)
The city of Gwangju in May 1980 was a scene of many atrocities committed in the name of state violence. The media, at the time, did not , or rather could not cover the carnage. The city of democratic struggle required a new writing of history. Artists include: Julie Mehretu, Mariam Ghani, Amar Kanwar
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions